G-104 Breaking the species barrier: IgG subclasses in man and macaques. (January 2016) - Chan, Ying; Boesch, Austin; Osei-Owusu, Nana; Cocklin, Sarah; Schmitz, Joern; Ackerman, Margaret
Abstract : Antibodies raised in Rhesus Macaques (Macaca mulatta, MM) in many preclinical vaccine studies are often evaluated in vitro for titer, antigen- recognition breadth, and neutralization potency or effector function, and in vivo for potential associations with protection. However, despite reliance on this key animal model in translation of promising candidates for evaluation in first in man studies, little is known about the properties of MM IgG subclasses and how they may compare to human IgG subclasses. We evaluated the binding of MM IgG1, IgG2, IgG3, and IgG4 to human FcγR and their ability to elicit the effector functions of human FcγR-bearing cells, and unlike in humans, find a notable absence of subclasses with relatively silent Fc regions. As inter- and intra-species differences in IgG sequence and function pose potential caveats to the translation of findings in these key animal models, understanding antibody immunobiology in primates may provide value in the design and evaluation of future vaccine candidates.